Analysis And Design Of Responsive Museum Portal Application With Flexbox And Grid-Based - Binti Abd Rahman, Aedah; Maulana, Haqi; Manaf, Khaerul (CV. Generasi Intelektual Digital, 2024)
The West Java People's Struggle Monument has an important role in preserving and disseminating information about the history of the struggle of the Indonesian people. In the digital era, the importance of an adequate digital presence to introduce and manage this information becomes increasingly apparent. This research aims to analyse and design a web-based responsive museum portal application at the West Java People's Struggle Monument using Flexbox and Grid responsive layout techniques in museum portal design. The existence of this website is expected to improve information management, as well as provide an optimal user experience through responsive and efficient user interface (UI) and user experience (UX) design. Therefore, this research focuses on fulfilling the digital needs of museums in overcoming information management challenges, so that this website can become an adequate and user-friendly marketing medium for introducing cultural and historical heritage to the public.